Application of Inorganic – Organic Eutectic PCM (Phase Change Material) to Improve Coolbox Efficiency - Nanda Yuniarti; Mifta Fatimah Supandi; Caecilia Pudjiastuti; Ketut Sumada; Stefano Ladini; Erwan Adi Saputro (Universitas Panca Marga, 2025)
The demand for efficient and environmentally friendly cold storage systems continues to increase, especially in the fisheries industry to maintain the quality of the catch. One alternative cooling medium is Phase Change Material (PCM), which is capable of storing and releasing energy in the form of latent heat during phase transitions. This study aims to evaluate the effectiveness of eutectic PCM composed of inorganic–organic materials in enhancing coolbox efficiency. The PCM was synthesized using food-grade ingredients: water, salt (NaCl), acetic acid, propylene glycol, and tapioca flour, and was then tested using Differential Scanning Calorimetry (DSC) and temperature profile analysis. Testing was conducted using various mass ratios of PCM to fish (from 1:1 to 4:1), and compared to conventional cooling media such as ice. The results showed that PCM with a 4:1 ratio was able to maintain temperatures in the range of -10°C to -0.4°C for 6 hours, with a total heat capacity of 1.4567 kJ/kg, significantly higher than that of ice (0.3120 kJ/kg). Furthermore, organoleptic tests indicated that fish stored with the 4:1 PCM remained fresh, scoring highest in aspects of odor, texture, and appearance. Therefore, the PCM developed in this study has proven to be more efficient in maintaining low temperatures and preserving fish quality compared to conventional cooling methods.